THE The Determinants of Accounting Students' Interest As An Accountant Educator : - - Nurhasanah, Siti Puji; Harahap, Ludwina (ADPEBI, 2024)
This study aims to determine the determinant of accounting students' interest to have a career as an accountant educator. To get data, we collected it from questionnaires to accounting students from 4 universities in South Jakarta with certain criteria. The questionnaires that were back and processed were 100. This study uses PLS analysis with a purposive sampling technique. In this research, the analytical tool used is Smart PLS 3.3.3 Software. The results show that variables of professional recognition, professional training, social values, and labor market consideration have a positive and significant effect on the interest of accounting students' careers as accountant educators.